Reporting of Ethical Issues in Indian Physiotherapy Journals - Sabapathy, S; Janakiraman, K; Srikesavan, C; Ayyanar (2009)
Background: Reporting of ethical issues in published articles not only improves the credibility of the journal and its published articles but also increases the confidence of the readers and general public. Purpose: The current study aimed to determine the current prevalence of reporting ethical issues in Indian Physiotherapy journals. Materials and methods: Two physiotherapy journals, the Journal of Indian Association of Physiotherapists (JIAP) and Indian Journal of Physiotherapy and Occupational Therapy (IJPOT) were searched for articles on human participants. The ethical issues expected to be reported were; ethical committee clearance, informed consent, photograph consent, and acknowledgements. Out of total 73 studies identified, 53 studies were from IJPOT (2007-2008) and 20 studies were from JIAP (2005-2008) and were included for final analysis. Analysis was done descriptively using percentiles for each of the four ethical issues. Results: Ethical committee clearance was mentioned in 14/73 studies (19.17%); informed consent in 38/68 studies, assent in 3/6 studies (50%), picture consent in 1/5 studies (20%), parent/guardian consent in 4/8 studies (50%) and acknowledgements in 8/73 studies (10.95%). Conclusion: The poor status of ethical reporting and lack of proper guidelines were evident in our findings. There is an immediate need for improving the situation considering the international reporting guidelines for research ethics. Key words: Physiotherapy, Publication, Ethical issues, Reporting.